Pola Komunikasi Tenaga Pendidik Dalam Membentuk Karakter Anak Di Usia Dini Pada Sekolah TK Negeri 1 Kapoa Kecamatan Kadatua (Khirani: Jurnal Pendidikan Anak Usia Dini, 2023)
There are several goals of communication patterns, one of which is to strengthen interpersonal ties between parties involved in the process. Information sharing and communication are important aspects of the educational process. In a communication-based learning process, both formal and informal, communication is packaged as beautifully as possible so that students at TK Negeri 1 Kapoa, Kadatua District can receive the message. The purpose of this research is to find out how early childhood teachers interact with their students and the elements that facilitate or hinder these interactions. The approach used in this research is descriptive qualitative, and the procedures used include interviews, observation and documentation to obtain data. data sources used in this case. As for the theoretical framework in this research, the author describes several definitions explaining the meaning of communication patterns, elements of communication, and forms of communication. The research results show that communication between educators and parents is currently running well and smoothly. Teachers and parents have the view that it is very important to instill character development from an early age to prepare children for life. Educators stated that parents responded very positively to matters related to character development. Likewise parents, educators provide support, advice and find solutions when parents face difficulties. Teachers and parents establish good communication so that there is a common view in character development. Thus, schools must establish good communication with students' parents or guardians.